Epigenetic regulation of RNA methylations in gastric cancer - Liu, Kaijie; Liu, Yafeng; Zhang, Shujun; Li, Ziang; Qu, Wenbing; Li, Penghui; Hu, Xinjun (Oncology Reviews, 2025)
Gastric cancer (GC) remains a major global health challenge due to its high incidence and mortality. Emerging evidence underscores the critical role of RNA methylation, a key layer of epigenetic regulation, in GC pathogenesis. This review synthesizes current knowledge on various RNA modifications, including m6A, m5C, m1A, and m7G, in GC. We critically evaluate the functions of their regulatory proteins (writers, erasers, readers) in modulating oncogenic signaling, metastasis, and tumor immunity. Among these, m6A and m5C modifications currently present the most compelling evidence, demonstrating significant correlations with patient prognosis and therapy resistance. Furthermore, we explore the translational potential of targeting the RNA methylation machinery, discussing both promising avenues and existing challenges in drug development. This comprehensive analysis aims to provide deeper mechanistic insights and highlight novel therapeutic opportunities for GC.